VASEKTOMI DALAM PANDANGAN ULAMA SALAF (STUDI ATAS PEMANDULAN MENURUT IBRAHIM AL-BĀJŪRĪ DAN JALĀLUDDĪN AL‑SUYŪṬĪ) - Subairi Subairi; Adib Ibrohimi (STKIP Pesisir Selatan, 2026)
This study examines the perspectives of two classical Islamic jurists, namely Ibrahim al-Bājūrī and Jalāluddīn al-Suyūṭī, regarding sterilization and its relevance to the medical procedure of vasectomy within the framework of Islamic law. The increasing use of vasectomy as a permanent contraceptive method in modern society has generated debate in relation to maqāṣid al-sharīʿah, particularly concerning the protection of lineage (ḥifẓ al-nasl). This research employs a qualitative method through classical text studies, analysis of Islamic legal maxims, and contextualization of Islamic law in contemporary conditions. The theories of maqāṣid al-sharīʿah and legal maxims proposed by both scholars serve as the analytical foundation of this study. The findings reveal that Ibrahim al-Bājūrī explicitly prohibited permanent sterilization because it eliminates reproductive potential, while temporary contraception is considered merely reprehensible (makrūh). Meanwhile, Jalāluddīn al-Suyūṭī, through the application of legal maxims prioritizing the lesser harm, allowed room for exceptions regarding sterilization in cases of necessity, such as threats to human life. Accordingly, permanent vasectomy is deemed prohibited (ḥarām), whereas reversible vasectomy performed under emergency circumstances may be permissible. This study highlights the importance of ijtihād in determining the legal status of modern contraceptive methods in order to remain aligned with the objectives of Islamic law (maqāṣid al-sharīʿah).